Structure‐Property Correlations in CZTSe Domains within Semiconductor Nanocrystals as Photovoltaic Absorbers - Ngoipala, Apinya; Ren, Huan; Ryan, Kevin M.; Vandichel, Matthias (Advanced science, 2024)
Semiconductor nanocrystals (NCs) are promising materials for various applications. Two of four recently identified CuαZnβSnγSeδ (CZTSe) domains demonstrate metallic character, while the other two exhibit semiconductor character. The presence of both metallic and semiconductor domains in one NC can hugely benefit future applications. In contrast to traditional band gap studies in the NC community, this study emphasizes that NC domain interfaces also affect the electronic properties. Specifically, the measured band gap of a tetrapod‐shaped CZTSe NC is demonstrated to originate from two specific domains (tetragonal I4¯$\bar 4$ and monoclinic P1c1 Cu2ZnSnSe4). The heterojunction between these two semiconductor domains exhibits a staggered type‐II band alignment, facilitating the separation of photogenerated electron‐hole pairs. Interestingly, tetrapod NCs have the potential to be efficient absorber materials with higher capacitance in photovoltaic applications due to the presence of both semiconductor/semiconductor interfaces and metal/semiconductor “Schottky”‐junctions. For the two photo‐absorbing domains, the calculated absorption spectra yield maximum photon‐absorption coefficients of about 105 cm−1 in the visible and UV regions and a theoretical solar power conversion efficiency up to 20.8%. These insights into the structure‐property relationships in CZTSe NCs will guide the design of more efficient advanced optical CZTSe materials for various applications. Four identified domains within tetrapod‐shaped CZTSe nanocrystals have distinct electronic properties. Interestingly, the 3D periodic structure of only two domains exhibits a band gap. Moreover, the computationally predicted type‐II band alignment between these two semiconductor domains facilitates electron‐hole pair separation and enhances solar power conversion efficiency. These insights enable optimizing the design of next‐generation CZTSe‐based solar cells and optoelectronic arrays.